Perbandingan Hasil Terjemahan Bahasa Arab Ke Bahasa Indonesia Dalam Penggunaan Chatgpt Dan Deepl Translator - Saniyah, Bahjatun; Azalia Yusri Filza, Luna; Aliyyah Salsabilah, Yasmin; Abas, Adzrah Dwi Sunarty (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research is motivated by the fact that developments in artificial intelligence technology have brought significant progress in the field of language translation, particularly from Arabic to Indonesian. However, the quality of translation results across platforms remains an interesting topic for study, particularly between ChatGPT and DeepL Translator, which both use AI-based models but with different approaches. The purpose of this study was to compare the quality of Arabic-to-Indonesian translations between ChatGPT and DeepL Translator. This research used a descriptive qualitative approach with a comparative study. Data were obtained through the translation of a number of Arabic texts selected through purposive sampling, consisting of common sentences, idioms, and cultural expressions. Translations were evaluated based on accuracy of meaning, readability, and contextual appropriateness. The results show that ChatGPT tends to produce translations that are communicative, contextual, and easily understood by Indonesian readers, while DeepL Translator is more literal and maintains the structure of the source language. ChatGPT excels in texts containing idioms and cultural nuances because it can adapt meaning to the context, while DeepL Translator is better suited for official documents or formal texts that require consistent sentence structure.